2023
DOI: 10.3847/1538-4357/acc52c
|View full text |Cite
|
Sign up to set email alerts
|

Seismological Studies of Pulsating DA White Dwarfs Observed with the Kepler Space Telescope and K2 Campaigns 1–8

Abstract: AllS single stars that are born with masses up to 8.5–10 M ⊙ will end their lives as white dwarf (WD) stars. In this evolutionary stage, WDs enter the cooling sequence, where the stars radiate away their thermal energy and are basically cooling. As these stars cool, they reach temperatures and conditions that cause the stars to pulsate. Using differential photometry to produce light curves, we can determine the observed periods of pulsation from the WD. We used the White Dwarf Evolution Code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…From stellar evolution calculations, we know that this is not physical (e.g., Córsico et al 2019). Hall et al (2023) performed the asteroseismic fitting of 29 DAVs observed with the Kepler and K2 missions. More physical, but still fixed, oxygen profiles were considered.…”
Section: Astrophysical Contextmentioning
confidence: 99%
“…From stellar evolution calculations, we know that this is not physical (e.g., Córsico et al 2019). Hall et al (2023) performed the asteroseismic fitting of 29 DAVs observed with the Kepler and K2 missions. More physical, but still fixed, oxygen profiles were considered.…”
Section: Astrophysical Contextmentioning
confidence: 99%
“…The two studies used different carbon-oxygen core structures, so it is not surprising that they found different solutions when it came to the helium and hydrogen layer masses. A more recent study using WDEC but with (still fixed) carbon-oxygen core profiles chosen to mimic those resulting from fully evolutionary models still found a majority of models with thinner hydrogen layers (23 out of 29; Hall et al 2023).…”
mentioning
confidence: 99%